2016
DOI: 10.1186/s12903-015-0139-y
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of 896 Oral squamous cell carcinomas from the only University based Oral Pathology Diagnostic Service in Sri Lanka

Abstract: BackgroundThe main objective of this study was to describe selected clinico-pathological characteristics of Oral Squamous Cell Carcinoma (OSCC) in Sri-Lanka.Materials & methodsThe study sample comprised of eight hundred and ninety six biopsies diagnosed as OSCC. The clinical and histopathological features were analyzed using the Chi-square test.ResultsOf the 896 biopsies, 801 were primary OSCCs, while 95 were recurrent OSCCs. Majority of the patients (78 %) were in the 5th to 7th decades of life and showed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 12 publications
6
58
3
Order By: Relevance
“…It is a complex and multistep process involving detachment of cells from the primary tumor, local invasion, entry into vasculature, proliferation, and evasion through the lymphatic system or blood vessels [15] . Previous studies have shown significant recurrence rates and frequent metastasis to cervical lymph nodes with OSCC [2,16] . Surgical removal of the primary tumor with neck dissection to remove affected lymph nodes is generally performed as treatment of OSCC [3] .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It is a complex and multistep process involving detachment of cells from the primary tumor, local invasion, entry into vasculature, proliferation, and evasion through the lymphatic system or blood vessels [15] . Previous studies have shown significant recurrence rates and frequent metastasis to cervical lymph nodes with OSCC [2,16] . Surgical removal of the primary tumor with neck dissection to remove affected lymph nodes is generally performed as treatment of OSCC [3] .…”
Section: Discussionmentioning
confidence: 95%
“…Surgical removal of the primary tumor with neck dissection to remove affected lymph nodes is generally performed as treatment of OSCC [3] . However, the majority of the clinically positive necks on histopathological evaluation do not show nodal metastasis [2] . Therefore it is mandatory to investigate parameters that would predict more accurately the presence of nodal metastasis prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a systemic disease is somehow related to many oral manifestations and reflected by the individual quality of life (QoL) [1-3]. Oral health also has a main contribution to the quality of life, and it directly affects people at their physical, cognitive, emotional, and social level [4].…”
Section: Introductionmentioning
confidence: 99%